Lower GI Bleeding and Left Colon Blue Rubber Blebs: Rare Case Report - Al-Lhedan, Fahad; Kurdi, Amr Mohammed (Archives of Clinical and Medical Case Reports, 2022)
A middle-aged male who is known to have acne vulgaris on oral treatment complaining of hematochezia containing blood clots for few weeks. The patient underwent colonoscopy displaying several left colon blue rubber blebs and here we are presenting this rare case.